Togo: Politics, economy and society in 2007 - Dirk Kohnert (Africa Yearbook Volume 4: Politics, Economy and Society South of the Sahara in 2007, 2008)
Togo's national reconciliation process initiated in 2006 continued in 2007. Largely free and fair parliamentary elections in October paved the way for the resumption of development aid after 14 years of interruption because of serious human rights violations and bad governance. The economic situation gradually improved in line with the resolution of the political crisis and the positive effects of the growing competition among global players for Africa's natural resources. However, the litmus test for the sustainability of the transition process will be the presidential elections of 2010, the only process capable of correcting the remaining democratic deficit bequeathed by the coup by the Gnassingbé-regime in 2005. – – Togos 2006 eingeleiteter nationaler Versöhnungsprozess wurde 2007 fortgesetzt. Weitgehend freie und faire Parlamentswahlen im Oktober ebneten den Weg für die Wiederaufnahme der Entwicklungshilfe nach 14 Jahren Unterbrechung aufgrund schwerer Menschenrechtsverletzungen und schlechter Regierungsführung. Die wirtschaftliche Lage verbesserte sich allmählich im Zuge der Lösung der politischen Krise und der positiven Auswirkungen des wachsenden Wettbewerbs der globalen Akteure um Afrikas natürliche Ressourcen. Der Lackmustest für die Nachhaltigkeit des Übergangsprozesses werden jedoch die Präsidentschaftswahlen 2010 sein, der einzige Prozess, der das verbleibende Demokratiedefizit beheben kann, das der Putsch des Gnassingbé-Regimes 2005 hinterlassen hat.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2007; domestic policy; foreign affairs; socio-economic development; period under review 2007